The Rib Cartilage Concept in Microtia - Frenzel, Henning (Facial Plastic Surgery, 2015)
There is a long history of rib cartilage use in reconstruction for microtia. This article aims to describe the modern techniques of autologous auricular reconstruction in detail, to elucidate the modifications for certain anatomical or disease-related conditions, and to contrast the different strategies used by other surgeons. The two mainstays of successful reconstruction with excellent results are the fabrication of the framework and soft tissue management. A three-dimensional framework mimics the curves, indentations, and peaks of a normal ear with maximal stability. Recently, the creation of a conchal bowl and an additional tragal strut has become a standard procedure. Soft tissue management is highly specific to each patient and equally contributes to the final result of the procedure. The correct position of the incision line and the trimming of the local flaps require thorough planning. Most of the individual modifications must be made in soft tissue management, particularly in patients with a low hairline and facial asymmetry. Autologous auricular reconstruction is a standard procedure that needs to be individualized to each patient. However, it is challenging and requires intensive training. In experienced hands, patients experience excellent results.
Keywords: ear; reconstruction; microtia; autologous; rib cartilage